2011
DOI: 10.1111/j.1447-0756.2011.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐N‐methyl‐D‐aspartate receptor encephalitis associated with ovarian immature teratoma

Abstract: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is a treatment-responsive encephalitis associated with anti-NMDAR antibodies. Unlike classic paraneoplastic encephalitis, this disorder usually develops in young women with ovarian teratoma who typically present with marked neuropsychiatric symptoms, followed by prolonged respiratory failure, clouding of consciousness, and bizarre dyskinesia. This disorder is often treatable by resection of ovarian tumor and immunotherapy, but, delayed diagnosis resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Approximately 60% of anti-NMDAR encephalitis symptoms are triggered by a tumor, mainly ovarian teratomas (mature, 70%; immature, 30%), but may be associated with sex cord stromal tumors or neuroendocrine tumors [5,7,8]. This condition has also been linked with testicular and mediastinal teratomas on rare occasions (5%) [5], In 40% of cases, no tumor is identified, but encephalitis symptoms persist [9].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Approximately 60% of anti-NMDAR encephalitis symptoms are triggered by a tumor, mainly ovarian teratomas (mature, 70%; immature, 30%), but may be associated with sex cord stromal tumors or neuroendocrine tumors [5,7,8]. This condition has also been linked with testicular and mediastinal teratomas on rare occasions (5%) [5], In 40% of cases, no tumor is identified, but encephalitis symptoms persist [9].…”
Section: Discussionmentioning
confidence: 92%
“…This condition has also been linked with testicular and mediastinal teratomas on rare occasions (5%) [5], In 40% of cases, no tumor is identified, but encephalitis symptoms persist [9]. In cases in which no tumor was identified, alternative etiologies such as a prodromal viral infection or genetic predispo sition were proposed [9,10], Patients who presented with a tumor displayed a stronger immune response to the condition than did those with no detectable tumor, and had better outcomes because of tumor excision [4,8,9], Lymphocytic pleocy tosis of the CSF is the most consistent finding in these patients [4,9], which is most likely attributed to the antibodies that are formed against the 2 subunits of the NMDA receptor, NR1 and NR2 [3,4,9,11], These heteromers bind glycine and glutamate, respectively, and are both required to form a functional receptor [2,4,7], The NR1 subunit is present throughout the CNS, which explains the wide variety of symptoms seen in patients with this syndrome [9,11], The NR2 NMDA receptors have a major role in synaptic transmission, remodeling, dendritic sprouting, hippocampal long-term potentiation, as well as memory formation and learning [2], The NR2 subunit is itself composed of 4 individual components, which are coded by specific genes and vary in their location and presence at different developmental stages [2,11],…”
Section: Discussionmentioning
confidence: 96%
“…[2][3][4] Similar paraneoplastic manifestations were noted in three patients with dysgerminomas. [6][7][8] Individual cases of paraneoplastic neurologic syndromes have also been reported in patients with teratomas [16][17][18] as well as hypercalcemia mediated by parathyroid-related protein 19 and a case of Cushing syndrome resulting from ectopic adrenocorticotropic hormone secretion caused by primary ovarian mature teratoma with carcinoid components. 20 Jaundice has only been previously reported in patients with ovarian carcinoma with metastatic disease to the hepatic hilar lymph nodes.…”
Section: Discussionmentioning
confidence: 94%
“…Our comprehensive review and experience can be summarized Author Sex/Age Outcome Sameshima et al [8] f/17 Complete recovery Massa et al [10] f/38 Partial remission with no consciousness with spontaneous eye opening Tachibana et al [11] f/21 Complete recovery Abdul-Rahman et al [12] f/25 Partial remission with memory impairment Wali et al [13] f/29 Partial remission with anterograde and retrograde amnesia Boeck et al [6] f/34 Partial remission with reduced cognitive function Imai et al [14] f/39 Complete recovery Braverman et al [15] f/12 Complete recovery Kleyensteuber et al [16] f/25 Partial remission with short term memory loss Naoura et al [17] f/27 Partial remission with attention deficits Kim et al [9] f/15 Complete recovery Frawley et al [18] f/11 Complete recovery Day et al [19] f/21 Patient expired ( cardiac arrest) Dulcey et al [20] f/20 Complete recovery Lo et al [7] f/21 Partial remission with dyskinesia, dysarthria, cognitive impairment Kawano et al [21] f/20 Complete recovery Yamanaka et al [22] f/27 Partial remission Johnson et al [23] f/35 Complete recovery Tanyi et al [24] f/34 Complete recovery f/24…”
Section: Resultsmentioning
confidence: 99%
“…Both studies reported significant impaired cognitive functions, reduced psychomotor status and parapresis of extremities [7]. Patients who had immediate tumor resection displayed a better outcome [8]. Corticosteroids were administered in 81.8% (16 studies) of cases.…”
Section: Case Reportmentioning
confidence: 99%